2023
DOI: 10.1186/s12882-023-03185-3
|View full text |Cite
|
Sign up to set email alerts
|

Karyomegalic interstitial nephritis as a rare cause of kidney graft dysfunction: case report and review of literature

Abstract: Karyomegalic interstitial nephritis (KIN) is a rare cause of chronic interstitial nephritis characterized by enlarged renal tubular epithelial nuclei. The first case of KIN reported in a kidney graft was in 2019. Here, we report the first case of KIN in 2 brothers receiving kidneys from 2 different unrelated living donors. A male kidney transplant recipient with focal segmental glomerulosclerosis as the original kidney disease presented with graft impairment and proteinuria, and graft biopsy revealed KIN. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The short stature, the striking leanness without any signs of a malignant disease, the café au lait color of the skin, the facial freckles, the hawk-like appearance of the nose, and mental capacity at the lower border of average or even below average were obvious features in patients B, C, D, and E. These abnormalities have not been discussed in earlier publications on KIN [ 17 , 18 , 27 , 28 , 29 ]. However, a focused review of the reports by us revealed a history of facial rash in one patient [ 20 ], atrophy and retraction of the left and right side of the nose in two patients [ 12 ], epilepsy in two patients [ 2 , 18 ], multiple sclerosis in one patient [ 8 ], and depression and emaciation in one patient [ 9 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The short stature, the striking leanness without any signs of a malignant disease, the café au lait color of the skin, the facial freckles, the hawk-like appearance of the nose, and mental capacity at the lower border of average or even below average were obvious features in patients B, C, D, and E. These abnormalities have not been discussed in earlier publications on KIN [ 17 , 18 , 27 , 28 , 29 ]. However, a focused review of the reports by us revealed a history of facial rash in one patient [ 20 ], atrophy and retraction of the left and right side of the nose in two patients [ 12 ], epilepsy in two patients [ 2 , 18 ], multiple sclerosis in one patient [ 8 ], and depression and emaciation in one patient [ 9 ].…”
Section: Discussionmentioning
confidence: 86%
“…The authors concluded that the KIN may represent recurrent KIN or donor-associated KIN, and in routine diagnostic practice, it can be mistaken for a viral infection. The interpretation of karyomegaly in the renal allograft is a challenging issue, indeed [ 27 ].…”
Section: Discussionmentioning
confidence: 99%